Faktor-Faktor yang Mempengaruhi Pendapatan dan Prospek Usahatani Ubi Kayu Varietas Lokal Nuabosi di Desa Randotonda Kecamatan Ende Kabupaten Ende - Willybrordus Lanamana; Philipus Nerius Supardi (Universitas Halu Oleo, 2020)
Cassava is a food substitute for rice to support community food security. Food availability is also determined by the level of farmer welfare as measured by income. This study aims to determine: (a) income rates of cassava farmers, b) factors affecting income rates of cassava farm; and (c) What is production trend of Nuabosi cassava. This research was conducted in Randotonda Village between November-January 2020. The population was 210 farmers. The sampling technique was simple random sampling, while the determination of the respondent used Slovin formula. The number of sample was 68 farmers. Multiple linear regression analysis was used to analyze the factors affecting income, and to forecast cassava production, the researcher used trend statistical analysis with regression analysis. The total income received by cassava farmers when they sold it to the district market was IDR 128.994.043 per ha and if they sold it famers’ garden was IDR 102.311.543 per ha. The variables that have a significant effect on cassava income and have a positive sign are the variables of land area, productivity, labor efficiency, dummy planting patterns, and the length of farming. The variable that has a significant and negative sign is the variable age. The development of Nuabosi cassava production and farm has an increasing trend. Nuabosi cassava farmers need to improve their cultivation techniques by using intercropping patterns, access prices for agricultural inputs and marketing.Keywords: Nuabosi cassava; income; production trend